Differential cross-sectional associations of work- and leisure-time sitting, with cardiorespiratory and muscular fitness among working adults - Madina Saidj; Torben Jørgensen; Rikke K Jacobsen; Allan Linneberg; Mette Aadahl (Nordic Association of Occupational Safety and Health (NOROSH), 2014)
OBJECTIVES: Sedentary behavior is increasingly recognized as a risk factor for cardiovascular and metabolic morbidity and mortality. Recent studies suggest that sitting during work and leisure time may affect markers of cardiometabolic health, differently. However, little is known about associations' between sitting time and cardiorespiratory and muscular fitness among adults. The aim of the present study was to examine associations between work- and leisure-time sitting, and key markers of cardiorespiratory and muscular fitness among working adults. METHODS: Working adults (N=2544) aged 18-69 from Health2006, a Danish population-based study, were included in this cross-sectional study. Sitting time during work and leisure time along with sociodemographic and behavioral covariates, including physical activity, were self-reported. Participants underwent a health examination with assessment of cardiorespiratory fitness (step test estimated VO_2Max, systolic and diastolic blood pressure) and muscular fitness (handgrip strength, lower limb extension power). Associations were explored by linear regression. Results Leisure-time sitting time was significantly (P<0.05) and inversely associated with VO_2Max, systolic blood pressure and handgrip strength among adults <50 years. There were no significant associations between sitting time at work and any of the markers of cardiorespiratory and muscular fitness. CONCLUSION: Work- and leisure-time sitting were differentially associated with cardiorespiratory and muscular fitness among working adults. This suggests that the domain in which sitting time is accrued should be considered when further investigating the relationship between sedentary behaviors and various healthy outcomes. In particular, caution should be exercised when labeling occupational sitting a danger per se for health.